The influence of blended learning-based learning model in invertebrate animal taxonomy course on learning outcomes - wita ferwati; Shabrina Rasyid Munthe (Institute of Computer Science (IOCS), 2023)
Blended Learning brings a paradigm shift in education, both for students and educators. This research will help identify the challenges and opportunities associated with implementing Blended Learning, so that it can be better adopted and adapted to enhance learning in the future. This study aims to determine the effect of the blended learning-based learning model on learning outcomes in the Invertebrate Animal Taxonomy course in semester 2 students of the biology education study program for the 2022/2023 academic year. The research method in this study was a quasi-experimental method, taking samples using a simple random sampling technique. The sample of this research was students in semester 2 of class A as an experimental class who were treated with a learning model based on blended learning and students in semester 2 of class B were given a conventional approach. The results of the research in this study are the learning outcomes of the Experiment class of 84 and the Control class of 70. The results of the t-test in this study obtained a tcount of 2.99 and table at a significant level of 5% of 2.00, then tcount > ttable based on this shows that the Blended Learning-Based Learning model influences student learning outcomes in the Invertebrate Animal Taxonomy course.